Poultry slaughterhouse wastewater as reservoirs for spreading extended-spectrum beta-lactamase-producing Escherichia coli in Abakaliki, Nigeria - EMMANUEL NNABUIKE UGBO; JENNIFER INIOBONG JACOB; MUSTOFA HELMI EFFENDI; ADIANA MUTAMSARI WITANINGRUM; BERNARD NNABUIFE AGUMAH; AGATHA IFUNANYA UGBO; BENJAMIN IKECHUKWU MOSES (Society for Indonesian Biodiversity, 2023)
Abstract. Ugbo EN, Jacob JI, Effendi MH, Witaningrum AM, Agumah BN, Ugbo AI, Moses BI. 2023. Poultry slaughterhouse wastewater as reservoirs for spreading extended-spectrum beta-lactamase-producing Escherichia coli in Abakaliki, Nigeria. Biodiversitas 24: 4960-4966. The emergence of antimicrobial and multi-resistance extended-spectrum beta-lactamase-producing organisms (ESBL) from the environment and hospitals is a serious global health concern. This research focused on the role of poultry slaughterhouse wastewater as a reservoir for spreading extended-spectrum beta-lactamase-producing Escherichia coli. Exactly 110 poultry slaughterhouses wastewater was collected using sterile universal containers from abattoirs in Abakaliki. The samples were analyzed microbiological for the presence of E. coli using standard techniques. The E. coli isolates found were subjected to a sensitivity test to antibiotics using the Kirby-Bauer disc diffusion method and further tested for ESBL-producing E. coli using a double disc synergy test and chromogenic media Brilliance ESBL agar. Of 110 wastewater samples analyzed, 55 (50.0%) were positive for E. coli contamination. The E. coli isolates showed antibiotic resistance ranging between 21.8% (amoxicillin clavulanic acid) to 69.1% (tetracycline), and good susceptibility was observed on cefepime (72.7%). Thus, among 55 E. coli isolates, 11(20.0%) were ESBL-producing E. coli with resistance patterns as follows: TET-STX-CAZ-CTX-FEP (four isolates); TET-STX-CAZ-CTX (four isolates); TET-STX-CAZ-CTX-FEP-CRO (three isolates), and average multidrug resistance index of 0.7. This study revealed that poultry slaughterhouse wastewater was a reservoir for multidrug resistance ESBL-producing E. coli. Therefore, properly treating wastewater from poultry production or farms before disposing into the drainage channel or water bodies is highly recommended to avoid spreading ESBL-producing organisms from animal waste products to humans and their environment.